PENGARUH KOLEKSI BUKU DAN PELAYANAN TERHADAP MINAT BACA SISWA PADA PERPUSTAKAAN SMP NEGERI 36 PURWOREJO (STIE Rajawali Purworejo, 2021)
The purpose of this research is to find out whether there is a positive and significant influence between book collections and services on students' interest in reading at the library of SMP Negeri 36 Purworejo. This research is quantitative descriptive research because research data uses numbers to conclude the results of research conducted at the library of SMP Negeri 36 Purworejo. The population of this study were all students at SMP Negeri 36 Purworejo, totaling 571 students. The sample used was 58 students using accidental sampling. This research used data analysis methods, namely: multiple linear regression, coefficient of determination, t test and F test. The results of calculating the coefficient of determination show an adjusted R Square figure of 0.131 or 13.1%. This figure means that 13.1% of students' reading interest is influenced by book collection and service variables. Meanwhile, the remaining 86.9% is influenced by other variables outside the research such as personality factors, gender, level of education, health, mental state and habits. This research shows the results of t tabel of 1.672, t hitung of the book collection variable of 1.962 with a sig value of 0.055 so that H1 is accepted . Meanwhile, t hitung service variable is 1.412 with a sig value of 0.163 so that H2 is rejected. The f test shows a figure of ƒ tabel3.158 with a confidence level of 0.05 and ƒ hitung of 5.371 with a sig value of 0.007, then H3 which states that simultaneously there is a positive and significant influence between the book collection and service variables on students' reading interest in the library of State Middle School 36 Purworejo is accepted and Hodi is rejected.